Wettability and work of adhesion of liquid sulfur on carbon materials for electrical energy storage applications. (March 2016) - Kaban, Ivan; Nowak, Rafał; Bruzda, Grzegorz; Xi, Lixia; Sobczak, Natalia; Eckert, Jürgen; Giebeler, Lars
Abstract: The wettability of glassy, microcrystalline and nanocrystalline carbon materials by liquid sulfur is studied by the sessile-drop technique applying the contact heating and drop-dispension procedures. Liquid sulfur shows a good wetting on all examined substrates just after melting, although the contact angle depends on the type and structure of the carbon material. Sulfur drops remain on the surfaces of glassy carbon and electrographite, whereas the liquid infiltrates into the substrates pressed from carbon micro- or nanoparticles. In the latter case, the infiltration rate increases along with decreasing size of particles used for preparation of the substrates, indicating a role of capillarity. The wetting and adhesion in the sulfur-carbon material systems are determined by the van der Waals interactions.